A Real Time IoT Measurement System for Hydroponics Cultivation - Sherubha, P.; Bharathipriya, C.; Iqbal, M. Mohammed; Ganesh, P.; Sasirekha, S. P. (2022 2nd International Conference on Computing and Information Technology (ICCIT), 2022)
Hydroponic cultivations are practiced in greenhouse or different plat factories. pH and electrical conductivity are commonly used to evaluate this type of farming. It may not deliver detailed information about any imbalances detected during the cultivation process. This results in a low yield or waste of resources. As a result, in order to overcome these constraints, in this cultivation process, an IoT measuring system must be installed, where actuators and sensors might assess the appropriate readings when needed and provided to human power. As a result, by constantly monitoring resources devoted to plant cultivation, an imbalance in nutrient acquisition is eliminated. This makes it easier for farmers to deal with nutrient concerns that arise during growing. The designed system's performance was computed in conjunction with the viability of an IoT framework for automated assessments. The results of the model are calculated and checked before being used in further processing. When there is no unique association among the standardized analyses, several specific metrics are explored. The sensitive responses are investigated and studied.